The prognostic value of p53 positive in colorectal cancer: A retrospective cohort study - Peng Wang; Jianwei Liang; Zheng Wang; Huirong Hou; Lei Shi; Zhixiang Zhou (Tumor Biology)
This retrospective cohort study aimed to discuss the prognostic value of p53 positive in colorectal cancer. A total of 124 consecutive patients diagnosed with colorectal cancer were evaluated at the National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College from 1 January 2009 to 31 December 2010. The expression of p53 in colorectal cancer was examined by immunohistochemistry. Based on the expression levels of p53, the 124 patients were divided into a p53 positive group and a p53 negative group. In this study, 72 patients were in the p53 positive group and 52 in the p53 negative group. The two groups were well balanced in gender, age, body mass index, American Society of Anesthesiologists scores, and number of lymph nodes harvested. p53 positive was associated with carcinoembryonic antigen ≥5 ng/mL ( p = 0.036), gross type ( p = 0.037), degree of tumor differentiation ( p = 0.026), pathological tumor stage ( p = 0.019), pathological node stage ( p = 0.004), pathological tumor–node–metastasis stage ( p = 0.017), nerve invasion ( p = 0.008), and vessel invasion ( p = 0.018). Tumor site, tumor size, and pathological pattern were not significantly different between these two groups. Disease-free survival and overall survival in the p53 positive group were significantly shorter than the p53 negative group ( p = 0.021 and 0.025, respectively). Colorectal cancer patients with p53 positive tended to be related to a higher degree of malignancy, advanced tumor–node–metastasis stage, and shorter disease-free survival and overall survival. p53 positive was independently an unfavorable prognostic marker for colorectal cancer patients.